MAKNA RISALAH DAN RELEVANSINYA DENGAN TANTANGAN DAKWAH - Safrizal; Nasrul Fatah (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
The writer is interested in discussing the meaning of the message in the Qur'an using a thematic method (maudhu'i), because not many can explain the meaning in a comprehensive way. Then the focus of this discussion is on the message spread in ten verses, namely: Al Maidah verses 67, Al An’am verses 124, Al A’raf verses 62, 68, 79, 93, 144, Al Ahzab verses 39, Al Jin verses 23 and 28. After conducting research and analysis of the interpretation of several mufasirs. It is clear that they do not differ in the meaning of the message in the Qur'an. The Messenger of Allah (peace and blessings be upon him) is the Messenger of all the people. All these messages are from God, and their primary purpose is to invite people to worship God and not to associate with Him.